PENINGKATAN KEMAMPUAN KOGNITIF MELALUI KEGIATAN PENCAMPURAN WARNA DI TK PGRI SUKADANA - Lia Ricka Pratama; Ai Netty Sumidartiny (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Cognitive development is an important aspect of early childhood education because it is related to children’s ability to think, understand, and solve problems. Based on observations conducted at TK PGRI Sukadana, it was found that children’s cognitive development had not developed optimally, especially in recognizing colors and understanding the concept of color mixing. This problem was caused by the lack of learning activities that actively involved children and the use of less interesting learning methods. Therefore, this study aimed to determine whether color mixing activities could improve early childhood cognitive development and to describe the process of improving cognitive development through color mixing activities at TK PGRI Sukadana. This study used a Classroom Action Research (CAR) method conducted in two cycles. The research subjects consisted of 26 children in Group B at TK PGRI Sukadana, including 14 boys and 12 girls. Data collection techniques were carried out through observation, documentation, and child development assessment. Data were analyzed using descriptive quantitative and qualitative methods to determine the improvement of children’s cognitive development in each cycle. The results of the study showed that color mixing activities were able to improve early childhood cognitive development. This was indicated by the decrease in the percentage of children in the Undeveloped category from 50% in Cycle I to 0% in Cycle II. Children also showed improvement in recognizing colors, distinguishing colors, and understanding that mixing two colors can produce a new color. The process of improving cognitive development occurred because children were actively involved in learning activities through observation, experimentation, and direct exploration. Thus, color mixing activities proved to be effective in improving early childhood cognitive development at TK PGRI Sukadana.